El Excentrico, 1954-08-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
August 20, 1954 [20 de agosto de 1954]. Ano 4, No. 20. Cover contains an flyer for a Latin American Day Party. Included in this flyer are photos of queen contest contestants, Lucy Serrano, Lydia Mendoza, Betty Hernandez, Leticia Villalobos, and Geraldine Beltran. The queen contest was hosted by the Civic Coodination Council.